Resource losses to Ukrainian tourism caused by full- scale Russian aggression - Liubitseva, Olga; Buchko, Zhanna; Patrusheva, Larysa; Kochetkova, Iryna (Kraków, 2023)
This article examines the concepts of urbicide and ecocide as a part of the violent policy against the state of Ukraine since the beginning of the full- scale Russian- Ukrainian war and their influence on tourism. We analyse their impact on natural recreational and tourist resources, such as land, air, river networks, and biotic and landscape diversity. Special attention is paid to protected areas of regional and national importance included in Ukraine’s ‘natural reserve fund’ and to sites of international importance that are part of the World Network of Biosphere Reserves. The article provides information about recorded crimes in different regions of Ukraine concerning historical and cultural heritage. Since 24 February 2022, at least 569 cultural heritage sites have been destroyed due to the war, including 170 monuments of national and local importance, 146 valuable historical buildings and cultural heritage sites, and 58 memorial monuments and works of art. We analyse losses in hospitality infrastructure relative to their zoning category determined by proximity to active fighting. The paper highlights the most urgent issues of the post- war restoration of Ukraine’s tourism sector, particularly facility staffing issues and ethical considerations when commemorating war events. Research methods: collection, analysis and the generalisation of information from official and research media sources concerning the loss of natural, historical, cultural and infrastructural resources suffered by tourism as a result of Russia’s military aggression in Ukraine from 24 Feb 2022 to 01 July 2023. Results: summary of the losses to tourism destination resources and infrastructure in Ukraine by region and type of impact, and a proposed framework for planning the post- war recovery of different kinds of tourism in Ukraine.
Keywords: ecocide; historical and cultural heritage; natural reserve fund; Russian- Ukrainian war; tourism; tourist infrastructure; urbicide